Sustainable synthesis of MgO nanoparticles from Persea americana for cultivar dependent nanostructure, environmental remediation and bioactivity supported by molecular docking - Badilli, Beyza Nur; Bulut Kocabas, Buket; Attar, Azade; Aktas, Emre; Altikatoglu Yapaoz, Melda (NATURE PORTFOLIO, 2026)
This study reports the sustainable green synthesis of magnesium oxide nanoparticles (MgONPs) using peel extracts from two avocado cultivars, Persea americana Mill. Hass and Fuerte, and demonstrates the strong influence of cultivar-dependent phytochemistry on nanoparticle properties and performance. UV-Vis spectroscopy confirmed MgONP formation with characteristic absorption bands at 220-280 nm, while FT-IR spectra revealed Mg-O stretching vibrations at 541 cm(-1) (Hass) and 552 cm(-1) (Fuerte), together with abundant hydroxyl and oxygen-containing functional groups derived from phytochemical capping agents. SEM analysis showed nanoscale particles (20-50 nm) forming porous and aggregated morphologies favorable for surface-mediated interactions. The synthesized MgONPs exhibited pronounced antibacterial and antifungal activity, with Fuerte-derived MgONPs producing larger inhibition zones (21 +/- 1 mm against Escherichia coli, 23 +/- 1 mm against Staphylococcus aureus, and 26.5 +/- 1 mm against Aspergillus niger). Molecular docking studies supported these findings, revealing exceptionally strong binding affinities of MgONPs toward key bacterial outer membrane proteins (- 14.1 to - 16.9 kcal/mol) and fungal targets, including 1,3-beta-glucan synthase (- 14.1 kcal/mol) and CYP51 (- 11.3 kcal/mol), surpassing those of reference antimicrobial agents. Environmental applicability was demonstrated through dye removal studies using five model dyes, where MgONPs showed dye-specific, dose-dependent removal with efficiencies exceeding 90% for selected dyes. Overall, Fuerte-derived MgONPs consistently outperformed Hass-derived counterparts, highlighting avocado peel-mediated MgONPs as efficient, low-cost, and multifunctional nanomaterials for antimicrobial and environmental remediation applications.
Keywords: Avocado; Environmental remediation; Magnesium oxide nanoparticles (MgONPs); Molecular docking; Persea americana; Sustainable nanotechnology; MAGNESIUM-OXIDE NANOPARTICLES; AQUEOUS-SOLUTION; TOXICITY; REMOVAL; GREEN; Science & Technology - Other Topics